2015
DOI: 10.1039/c4cc08007f
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid of titanium nitride and nitrogen-doped amorphous carbon supported on SiC as a noble metal-free electrocatalyst for oxygen reduction reaction

Abstract: A novel noble metal-free catalyst, with nitrogen-doped amorphous carbon and titanium nitride particles supported on SiC (NC-TiN/SiC), was synthesized. The NC-TiN/SiC catalyst exhibited excellent oxygen reduction reaction activities as well as superior stability and methanol tolerance. The catalytic activities were attributed to the synergistic effect of TiN and NC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Heringa et al (2016) and Rompelberg et al (2016) published an overview of studies examining the absorption of ingested TiO 2 nanoparticles [ 1 , 49 ]. Following their physiologically based pharmacokinetic (PBPK) modeling, these researchers concluded that TiO 2 nanoparticles can be absorbed, although at a very small rate of approximately 0.02 to 0.05% [ 51 , 71 , 72 , 73 ]. The translocation into lymphatic and blood circulation can lead to the deposition of TiO 2 nanoparticles within tissues and organs after ingestion [ 71 ].…”
Section: Toxicokinetics Of Ingested E171mentioning
confidence: 99%
“…Heringa et al (2016) and Rompelberg et al (2016) published an overview of studies examining the absorption of ingested TiO 2 nanoparticles [ 1 , 49 ]. Following their physiologically based pharmacokinetic (PBPK) modeling, these researchers concluded that TiO 2 nanoparticles can be absorbed, although at a very small rate of approximately 0.02 to 0.05% [ 51 , 71 , 72 , 73 ]. The translocation into lymphatic and blood circulation can lead to the deposition of TiO 2 nanoparticles within tissues and organs after ingestion [ 71 ].…”
Section: Toxicokinetics Of Ingested E171mentioning
confidence: 99%
“…Additional reduction products such as titanium oxycarbides (TiO 1Àx C x ) which are typically formed in an excess of carbon are not identified in the investigated temperature range.D ue to the usage of melamine in the synthesis of metal nitrides,t he formation of titanium oxynitrides (TiO 1Àx N x )ornitrides (TiN) might be possible as well. [16] At 1000 8 8Cthe presence of rocksalt structured titanium (oxy-)nitride phase ( Figure S4a, empty squares), which starts to appear at 700 8 8C, is also possible.R emarkably,t he diffraction peaks which were assigned to this phase do exhibit as hift to smaller angles 2 theta if the pyrolysis temperature is increased to 1000 8 8C. This finding leads to the assumption that pure TiNi sf ormed at 1000 8 8Cf rom the titanium oxynitrides which is present after treatment at lower temperatures.B eside the reduction of titania the ongoing crystal growth of metallic cobalt can be stated (cf.4 .6 nm at 800 8 8C, 10.3 nm at 1000 8 8C).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Furthermore,t oi nvestigate the chemoselectivity for this hydrogenation process,p yridines bearing phenyl, benzyl, amide or acid groups were tested. Here,3 -, and 4-phenylpyridine as well as 2-benzylpyridine were hydrogenated to the corresponding piperidines without hydrogenation of the phenyl ring ( Table 1, entries [14][15][16]. Additionally,i sonicotinamide and isonicotinic acid were successfully converted to piperidine-4-carboxamide (2m)and piperidine-4-carboxylic acid (2n)s imply using water as solvent (Table 1, entries 17,18).…”
Section: Zuschriftenmentioning
confidence: 99%
“…The Na 2/3 Fe 1/2 Mn 1/2 O 2 ‐G cathode exhibits a wide plateau around 4.1 V and is thus a suitable cathode material. Regarding graphene alone, electrochemical performance enhancement through nitrogen doping has been reported . Three different positions of N (pyridinic N, pyrrolic N, and quaternary N) and their effects on SIB performance were explored (Figure f) .…”
Section: Heterogeneous Nanostructures For Sodium Ion Batteriesmentioning
confidence: 99%
“…Regarding graphene alone, electrochemical performance enhancement through nitrogen doping has been reported. [58,59] Threed ifferent positions of N( pyridinic N, pyrrolic N, and quaternary N) and their effects on SIB performance were explored (Figure 3f). [53] Doping withp yrrolic Ni sd emonstrated to facilitate ion movement with the highest efficiency (capacity retention of 93 %o ver 200 cycles and lowest capacity drop (ca.…”
Section: Sib Cathode Materialsmentioning
confidence: 99%